Reading with Eyes Wide Open: Reflections on the Impact of Multimodal Texts on Second Language Reading - Farias-Farias, M (Universidad de Antioquia, 2017)
In the context of what has been called a new sociosemiotic landscape in communications, this article explores how reading multimodal texts demands a change in literacy practices and reflects on the impact of these changes on second language reading. We review the literature that has incorporated multimodal texts in the discussion of second language reading and evaluate it in light of the practices second language readers engage in when comprehending multimodal texts. Implications of this transition from understanding reading as an individual, text-based, and univocal activity to approaching it as literacy practice are included. We finish with reflections and conclusions derived from such explorations.